"Women under the radar": the intersection of migration and domestic violence explored through the framework of "(un)deservingness" - Creswick, Helen Emma (2017)
Victims of domestic violence may commonly be constructed as ‘deserving’ of state support, however the intersection of migration and domestic violence complicates such matters, often rendering migrant women with an irregular immigration status as ‘undeserving’. This thesis bridges the gap between literatures on migration and domestic violence by using the framework of ‘(un)deservingness’ to explore the lives of women with an irregular immigration status who experience domestic violence. Interviews were conducted with women with an irregular immigration status, primarily focusing on those who overstay their visas, as well as professionals who provide support to women.